2021
DOI: 10.1186/s12876-021-01766-w
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid endoscopic submucosal dissection: An alternative resection modality for large laterally spreading tumors in the cecum?

Abstract: Background Endoscopic resection for large, laterally spreading tumors (LSTs) in the cecum is challenging. Here we report on the clinical outcomes of hybrid endoscopic submucosal dissection (ESD) in large cecal LSTs. Methods We retrospectively reviewed data from patients with cecal LSTs ≥ 2 cm who underwent ESD or hybrid ESD procedures between January of 2008 and June of 2019. We compared the baseline characteristics and clinical outcomes, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Previous reports on the clinical outcomes of hybrid ESD and C-ESD for colorectal lesions are summarized in Table 4. 11,17,[19][20][21][22][23][24][25][26] Although several studies have shown that the en bloc resection rate is significantly lower with the use of hybrid ESD techniques (56.8%-94.1%) than with the use of C-ESD techniques (81.5%-100%), most did not classify hybrid ESD into preplanned SH-ESD and unplanned RH-ESD. [18][19][20]22 In general, planned SH-ESD is used for relatively small tumors that can be easily snared, whereas unplanned RH-ESD is used for lesions that are difficult to resect.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports on the clinical outcomes of hybrid ESD and C-ESD for colorectal lesions are summarized in Table 4. 11,17,[19][20][21][22][23][24][25][26] Although several studies have shown that the en bloc resection rate is significantly lower with the use of hybrid ESD techniques (56.8%-94.1%) than with the use of C-ESD techniques (81.5%-100%), most did not classify hybrid ESD into preplanned SH-ESD and unplanned RH-ESD. [18][19][20]22 In general, planned SH-ESD is used for relatively small tumors that can be easily snared, whereas unplanned RH-ESD is used for lesions that are difficult to resect.…”
Section: Discussionmentioning
confidence: 99%
“…However, the limited data on H-ESD renders its com- parison with conventional ESD (C-ESD) difficult (Fig. 6 Hybrid endoscopic resections can be perfomed in different ways. Specific terminologies have been previously described and must be used to distinguish the various forms of this approach.…”
Section: Open Accessmentioning
confidence: 99%
“…Capturing a too large portion of submucosa may deform attached layers, leading to unplanned cutting levels with a higher risk of damage to the muscularis propria or fragmentation of the lesion. 6 When faced with difficult situations, such as severe fibrosis, prolonged procedure time, large perforations, massive bleeding, and unstable vital signs, endoscopists should be ready to shift from the C-ESD to RH-ESD for faster resolution of the procedure. Prolonged or complicated endoscopic procedures can influence the physician's decision-making process and focus and have a higher physiological impact on the patient.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the remaining lesion is completely resected with a snare. 56 A study on small (≤20 mm) early gastric neoplasms revealed that the hybrid technique has a shorter procedure time (33 minutes vs. 62 min-utes), with comparable curability and safety, when compared to ESD (possible lower thermal damage to the submucosal layer in H-ESD). 57 A shorter procedure time was observed for H-ESD, when compared to conventional ESD, for colonic lesions, with a lower en bloc and R0 resection rate.…”
Section: Is Esd Always Necessary?mentioning
confidence: 99%